Chloride (Cl−) ion-mediated shape control of palladium nanoparticles. (14th January 2016) - Nalajala, Naresh; Chakraborty, Arup; Bera, Bapi; Neergat, Manoj
Abstract: The shape control of Pd nanoparticles is investigated using chloride (Cl − ) ions as capping agents in an aqueous medium in the temperature range of 60–100 °C. With weakly adsorbing and strongly etching Cl − ions, oxygen plays a crucial role in shape control. The experimental factors considered are the concentration of the capping agents, reaction time and reaction atmosphere. Thus, Pd nanoparticles of various shapes with high selectivity can be synthesized. Moreover, the removal of Cl − ions from the nanoparticle surface is easier than that of Br − ions (moderately adsorbing and etching) and I − ions (strongly adsorbing and weakly etching). The cleaned Cl − ion-mediated shape-controlled Pd nanoparticles are electrochemically characterized and the order of the half-wave potential of the oxygen reduction reaction in oxygen-saturated 0.1 M HClO4 solution is of the same order as that observed with single-crystal Pd surfaces.